Turbulence impacts upon nvPM primary particle size. Issue 10 (6th September 2022) - Vander Wal, Randy; Singh, Madhu; Gharpure, Akshay; Choi, Cindy; Lobo, Prem; Smallwood, Greg
Abstract: Originating from an IAE V2527 aircraft gas turbine engine running a series of reference and blended fuels, nonvolatile particulate matter was collected upon transmission electron microscopy grids for analysis. A striking observation is the range of primary particle size with projected particle diameters ranging from 5 to 100 nm within the same aggregate. This range of particle size is interpreted as describing the corresponding ensemble of fuel rich pockets in terms of fuel-air-equivalence ratio (Φ) and duration. Some parcels are sufficiently diluted or short-lived by turbulent action and allow only small primary particles to form. Other parcels are larger, live longer or a combination allowing large primary particles to form. In this manner, the soot particles provide forensic insights into the turbulent mixing dynamics. Consequently, there is no single streamline or trajectory describing particle growth and no single condition in Φ or temperature for particle nucleation. There is also no observable correspondence between particle size and fuel aromatic or hydrogen content. Given the different trajectories of small/large particles, their growth histories and species origins, a difference in H/C ratio would be expected. This is reflected in the relative contributions of sp 2 /sp 3 content within the particles as confirmed by electron energy loss spectroscopy analysis. Supporting evidence for the role of turbulent induced mixing upon primary particle growth is evidenced by varied particle size modes for XC-72, oxidation reactivity of R250, both commercial furnace blacks. Further confirmation is found by pulsed laser derivatization of XC-72. Copyright © 2022 American Association for Aerosol Research Graphical Abstract: UF0001